2011
DOI: 10.1177/1744259111403440
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of the thermal performance of light steel residential buildings in Csb climatic regions

Abstract: In this article, the passive thermal performance of a light steel residential building is studied. A numerical model is implemented and is experimentally validated. The analysis is focussed on the Csb climatic region. Subsequently, this calibrated model is used to assess the importance of several parameters (ventilation, thermal insulation, overhangs shading, windows shade devices, and windows glazing) in the summer and winter thermal performance of this building. Subsequently, based on the cooling and heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Noting that the conclusions from this paper relate to a specific climate zone (Csb, representative of Southern Europe (Santos et al (2011)), and were obtained for a specific sub-sector of the construction sector (low-rise residential), the following aspects are highlighted:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noting that the conclusions from this paper relate to a specific climate zone (Csb, representative of Southern Europe (Santos et al (2011)), and were obtained for a specific sub-sector of the construction sector (low-rise residential), the following aspects are highlighted:…”
Section: Discussionmentioning
confidence: 99%
“…in comparison with the traditional construction techniques (Santos et al 2010). Light-weight steel construction solutions for low-rise residential buildings are very light, exceptionally solid in relation to weight, provide easier architectural typological flexibility and adaptability, present excellent stability of shape in case of humidity, excellent thermal behaviour (Santos et al 2011), and rapid on-site erection, are easy to prefabricate allowing for better quality control, and offer great potential for recycling and reuse. Furthermore, the number of companies specialised in executing these types of solutions is increasing and the prices are becoming more competitive, leading to a fast-growing market share, not only in Portugal but all over the world (European Lightweight Steel-framed Construction 2005).…”
Section: Calibration Against Cfd Simulationsmentioning
confidence: 99%
“…Air tightness is very important in cold climates to control heat losses due to air infiltrations [32,33]. Kalamees measured the air tightness and air leakages of new lightweight single-family detached houses in Estonia and concluded that the number of storeys and the quality of workmanship and supervision play a significant role in the condition of air tightness [33].…”
Section: Wind and Air Tightness Membranesmentioning
confidence: 99%
“…Furthermore, some additional case studies related to LSF buildings thermal behaviour and energy eiciency will be described, namely the "Afordable Houses" research project [5,6], a parametric study regarding the thermal performance of LSF houses in Csb climatic regions [28], the impact of climate change on the energy eiciency of a LSF residential building [9] and the optimization of incorporation of PCMs in LSF houses in diferent climates [25].…”
Section: Case Studiesmentioning
confidence: 99%
“…with the cooling/heating systems turned of). Santos et al [28] performed a parametric analysis of the passive thermal performance of LSF residential buildings in Csb climatic regions located in southern European countries. With that purpose, a Portuguese low-rise residential building (Figure 18) was monitored in terms of its thermal behaviour, and an advanced dynamic DesignBuilder model was assembled (Figure 18c, d), calibrated and validated making use of the in situ recorded data.…”
Section: Passive Thermal Performance In Csb Climatic Regionsmentioning
confidence: 99%